Drug therapy problems and contributing factors among patients with epilepsy. - Yirga Legesse Niriayo; Tesfay Gebregziabher; Gebre Teklemariam Demoz; Nigusse Tesfay; Kidu Gidey (PLoS ONE, 2024)
Background Although antiseizure medications play a crucial role in the management of epilepsy, their benefit can be compromised due to drug-related problems. Drug therapy problems can lead to poor seizure control, reduced quality of life, and increased morbidity and mortality in patients with epilepsy. However, in our setting, there is limited knowledge about drug therapy problems and the factors that contribute to them. Objective The aim of this study was to investigate the prevalence and contributing factors of drug-therapy problems among patients with epilepsy. Methodology A hospital-based prospective observational study was conducted at the neurologic clinic of Ayder Comprehensive Specialized Hospital, located in the Tigray region of Northern Ethiopia. The study included adult patients diagnosed with epilepsy who had been taking at least one antiseizure medication for a minimum of six months. Data were collected by conducting patient interviews and expert reviews of medical and medication records. Prior to data review and interviews, each patient provided written informed consent. Drug therapy problems were identified and classified using Cipolle's method, followed by a consensus review conducted with a panel of experts. Statistical analysis was performed using a statistical software package; SPSS version 22. Binary logistic regression analysis was conducted to determine the contributing factors of drug therapy problems. Statistical significance was determined at p<0.05. Results A study conducted on 250 participants revealed that 55.2% of the patients experienced one or more drug therapy problems. Our analysis identified a total of 282 drug therapy problems, with a mean of 2±0.52 drug therapy problems per patient. The most commonly observed drug therapy problems were dosage too low (30.0%), noncompliance (22%), adverse drug reaction (18%), and unnecessary drug therapy (16.4%). The commonly involved antiseizure medications in these drug therapy problems were phenytoin (22.8%), Valproic acid (20.8%), and Phenobarbital (18.4%). Furthermore, our findings revealed that combination therapy (AOR: 3.92, 95%CI: 1.19-12.97) and uncontrolled seizure (AOR: 108.37, 95%CI: 38.7-303.6) exhibited significant associations with drug therapy problems. Conclusion Drug therapy problems were prevalent among patients with epilepsy. The use of combination therapy and the presence of uncontrolled seizures were identified as significant indicators of drug therapy problems. Therefore, more emphasis should be given to patients with multiple medications and uncontrolled seizures.